Association of Pre-Treatment Serum Testosterone Levels with Prostate Cancer: A Prospective Study - Sharma, Vishnukant; Mavuduru, Ravimohan Suryanarayan; Bora, Girdhar Singh; Sharma, Aditya Prakash; Devana, Sudheer Kumar; Rastogi, Ashu; Kakkar , Nandita; Singh , Shrawan Kumar (International Journal of Clinical Research, 2024)
Introduction: It has been widely accepted that prostate cancer (PCa) growth is related to serum testosterone (ST). A direct correlation between pre-treatment ST level and PCa growth and progression has been reported. However, recent studies have shown that pre-treatment ST levels have a negative correlation with PCa. Thus, the literature is, at best, conflicting. In this study, we examined the pre-treatment serum total testosterone (ST) levels in PCa. Methods: In this prospective observational study, suspected cases of PCa underwent digital rectal examination, routine blood investigation, Prostate-Specific Antigen (PSA) measurement, and prostate biopsy. Diagnosed cases of PCa without any risk factors affecting testosterone levels were included. Their pre-treatment total ST levels were measured. All patients underwent staging evaluation with either Magnetic Resonance Imaging (MRI) & Bone scan or Ga-68 Prostate Specific Membrane Antigen Positron Emission Tomography (PSMA PET). ST levels were also measured in patients with Benign Prostatic Hyperplasia (BPH) and compared with those in PCa patients. ST levels were also assessed according to Gleason Score (GS) and clinical stage in PCa. Results: 110 cases and 54 patients with BPH were included in the study. The median ST level in PCa patients was significantly lower as compared to BPH patients [352.28 ng/dL (Interquartile Range (IQR) 224.99-563.17) vs. 448.29 ng/dL (IQR 400.97-596.42) (p =0.004)]. The median ST level in metastatic PCa was significantly lower than the localized PCa group [298.20 ng/dL vs. 452.30 ng/dL (p=0.0001)]. Moreover, the median ST level was also significantly lower in patients with Gleason Score ≥ 8 than those with Gleason Score ≤ 7 [285.92 ng/dL (149.97-560.40) vs. 425.13 ng/dL (320.43-571.46) (p=0.002)]. Conclusion: This study shows lower ST levels in patients with PCa compared to patients with BPH, thus supporting a potential association as described in previous studies. ST levels may have prognostic value since a low pre-treatment ST level is associated with a higher clinical stage and aggressive PCa.